Answering opinion questions on products by exploiting hierarchical organization of consumer reviews - Yu, J. (2014)
EMNLP-CoNLL 2012 - 2012 Joint Conference on Empirical Methods in Natural Language Processing and Computational Natural Language Learning, Proceedings of the Conference